THE EFFECT OF HUMAN CAPITAL ON INNOVATION OF SMALL AND MEDIUM-SIZED ENTERPRISES IN VIETNAM - Bao, Mai (International Journal of Management and Allied Research (IJMAR), 2023)
This study aims to examine the effect of human capital on innovation of small and medium-sized enterprises in Vietnam in the competitive environment. The study uses the data collected by Central Institute for Economic Management (CIEM) in 2011, 2013 and 2015. By using the Tobit model, the results show that human capital positively influence innovation of Small and Medium-sized Enterprises (SMEs). Base on the findings, small and medium firms in Vietnam need to adopt an effective training program as well as developing a virtuous labour network in order to enhance human capital as a result motivating companies’ innovation output, which embrace new products, new process and modified products.